The Deletion of GluK2 Alters Cholinergic Control of Neuronal Excitability. (3rd November 2021) - Gorlewicz, Adam; Barthet, Gael; Zucca, Stefano; Vincent, Peggy; Griguoli, Marilena; Grosjean, Noëlle; Wilczynski, Grzegorz; Mulle, Christophe
Abstract: Kainate receptors (KARs) are key regulators of synaptic circuits by acting at pre- and postsynaptic sites through either ionotropic or metabotropic actions. KARs can be activated by kainate, a potent neurotoxin, which induces acute convulsions. Here, we report that the acute convulsive effect of kainate mostly depends on GluK2/GluK5 containing KARs. By contrast, the acute convulsive activity of pilocarpine and pentylenetetrazol is not alleviated in the absence of KARs. Unexpectedly, the genetic inactivation of GluK2 rather confers increased susceptibility to acute pilocarpine-induced seizures. The mechanism involves an enhanced excitability of GluK2 −/− CA3 pyramidal cells compared with controls upon pilocarpine application. Finally, we uncover that the absence of GluK2 increases pilocarpine modulation of Kv7/M currents. Taken together, our findings reveal that GluK2-containing KARs can control the excitability of hippocampal circuits through interaction with the neuromodulatory cholinergic system.